2014
DOI: 10.1002/ctpp.201400061
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Direct Double Auger Decay on the Population Dynamics of Neon Irradiated by Ultraintense x‐ray Pulses

Abstract: The population and charge state distribution of neon interacting with ultraintense x-ray pulses are investigated by solving a time-dependent rate equation in the detailed level-accounting (DLA) approximation. Due to the detailed description of neon atom and ions, our DLA result improves the agreement between predictions and experimental measurements for odd neon charge states. In the framework of the DLA formalism, we further studied the effects of direct double Auger decay (DDAD) on charge state distribution.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 29 publications
(46 reference statements)
1
24
0
Order By: Relevance
“…Our choice of parameters produces a peak intensity of 2.2 × 10 17 W cm 2 which is consistent with 4.5 × 10 17 W cm 2 at a FWHM pulse duration of 140 fs used in Ref. 35 to produce similar theoretical ion yields as the ones shown in the lower panel with the modified rate equations. To achieve about the intensity of Ref.…”
Section: Ion Yields Of Neon Atomssupporting
confidence: 83%
See 4 more Smart Citations
“…Our choice of parameters produces a peak intensity of 2.2 × 10 17 W cm 2 which is consistent with 4.5 × 10 17 W cm 2 at a FWHM pulse duration of 140 fs used in Ref. 35 to produce similar theoretical ion yields as the ones shown in the lower panel with the modified rate equations. To achieve about the intensity of Ref.…”
Section: Ion Yields Of Neon Atomssupporting
confidence: 83%
“…Subsequent theoretical research [17,34,35] revealed that there are substantial further many-electron effects in neon in this case. Specifically, shake off following K-shell ionization [17] and double Auger decay of a K-shell vacancy [35] were included in extended rate-equation models for neon. This mitigated substantially the discrepancy found between the ion yields from the experiment and the plain rate equations.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations